GE_GERICHTE P/16050/2008 vom 19. Februar 2018 - GE Cour de justice (2018)
DÉCISION DE RENVOI ; INDEMNITÉ(EN GÉNÉRAL) ; USAGE DE FAUX(DROIT PÉNAL) ; OBTENTION FRAUDULEUSE D'UNE PRESTATION | CPP.409; CPP.135.al1; CP.251; CP.253